Improving Image Inpainting through Contextual Attention in Deep Learning - Charef, Ayoub; Ouqour, Ahmed (Engineering, Technology & Applied Science Research, 2024)
Image processing is vital in modern technology, offering a diverse range of techniques for manipulating digital images to extract valuable information or enhance visual quality. Among these techniques, image inpainting stands out, involving the reconstruction or restoration of missing or damaged regions within images. This study explores advances in image inpainting and presents a novel approach that integrates coarse-to-fine inpainting and attention-based inpainting techniques. The proposed method leverages deep learning methods to enhance the quality and efficiency of image inpainting, achieving robust and high-quality results that balance structural integrity and contextual coherence. A comprehensive evaluation and comparison with existing methods showed that the proposed approach had superior performance in maintaining structural integrity and contextual coherence within images.